TRAINING FOR DEVELOPING VILLAGE REGULATIONS TO SUPPORT THE POTENTIAL DEVELOPMENT OF MEKARSARI ECOWISATA VILLAGE - Winayati, Nia K.; Tuti Rastuti; Utari Dewi Fatimah; Gandhi Phramacista (Pasundan International of Community Services Journal (PICS-J), 2024)
Mekarsari Village is one of ten tourist villages in Bandung Regency, which has the potential to be developed into an eco-tourism village. However, this potential has not been maximized because village government governance to support the development of village potential is still inadequate. One of the crucial things in village governance is the legal umbrella in the form of village regulations that are aspirational and responsive to accommodate the interests of the community. Against the urgency of forming village regulations, it is necessary to conduct training activities on the preparation of village regulations that involve community participation. The activity aims to increase the capacity of village officials, village consultative bodies (BPD), and the community to draft village regulations. Based on the observations, the following problems can be identified; (1) The draft village regulations have not been stipulated in the Mekarsari Village Government Work Plan (RKP); (2) the capacity of relevant individuals in mastering the systematic preparation of the village regulations has not been maximized. The method used is Participatory Action Research (PAR) through three stages of activities, namely planning, implementation, and evaluation activities. The whole activity ran smoothly, and the target audience enthusiastically participated in the activity, increasing the target's ability to make and draft village regulations.